Comparison of search and rescue operations involving emergency physicians in devastating earthquakes in Turkey: a 24-year experience study - Mustafa Ferudun Celikmen; Gülbin Aydoğdu Umaç; Melih Imamoglu; Mümin Murat Yazici; Elif Çiğdem Keleş; Sarper Yilmaz (BMC Emergency Medicine)
Abstract Background In the 21st century, disasters (particularly earthquakes, which remain the leading cause of death) continue to be among the foremost issues requiring global emergency response. While the impact of advancing technologies on the environmental and human damage caused by earthquakes is still a subject of debate, search and rescue (SAR) teams and emergency departments (ED), specifically emergency physicians (EPs), play a crucial role in the most acute management of the effects of these earthquakes on human life. This study aims to examine the injury dynamics of two catastrophic earthquakes that occurred in Turkey 24 years apart from the perspective of EPs, utilizing archival records from the SAR teams in which EPs served. Method This study is a cross-sectional investigation analyzing the injury and SAR dynamics of casualties, based on the archives of SAR teams that included 12 EPs, during the 1999 Marmara and 2023 Kahramanmaraş (Maraş) earthquakes (groups). Results In this study, a total of 160 injured individuals who were rescued alive from the rubble were included, with 26.3% (n = 42) from the Maraş group and 73.8% (n = 118) from the Marmara group. Identification of the injured was achieved in 54.8% (n = 23) of the Maraş group and 88.1% (n = 104) of the Marmara group, with an overall identification rate of 79.4% (n = 127) (p < 0.001). The most common injuries among the injured were lower extremity injuries (53.1%, n = 85) and upper extremity injuries (49.4%, n = 79), with the most frequent scenario being the extraction of two individuals from the same location (33.8%, n=54). The most common interventions provided to the injured were intravenous fluid therapy (63.8%, n =102) and oxygen support (57.5%, n =92). The rate of intubation at the scene was 16.1% (n = 19) in the Marmara group and 4.8% (n = 2) in the Maraş group (p < 0.05). Additionally, cardiopulmonary resuscitation (CPR) was administered at the scene in 13.6% (n = 16) of the Marmara group, compared to 2.4% (n = 1) in the Maraş group (p < 0.05). When examining the challenges encountered during SAR operations, the most frequent issue in the Maraş group was identification, affecting 57.1% of the cases (p < 0.001), whereas the most common issue in the Marmara group was entrapment, occurring in 50.0% of cases (p < 0.001). Lighting difficulties were observed at similar rates in both earthquakes (19.0% in Maraş, 19.5% in Marmara; p = 1.000). Additionally, weather conditions posed a challenge in 11.9% of cases in the Maraş group, whereas this issue was not encountered in the Marmara group (p < 0.001). Conclusion The 24 years of experience and expertise gained by EPs who served in Türkiye in these operations constitute a valuable global resource. Disseminating this knowledge is crucial not only for managing earthquakes but also for preparing for other catastrophic events that could cause widespread destruction. Harnessing this accumulated experience can significantly enhance knowledge-sharing and the development of more effective preparedness strategies.